Determinants of athlete motivation and engagement in collegiate team sports: Toward a sports development framework - Panganiban, Teejay D.; Nabor, Samboy (Physical Education and Sports: Studies and Research, 2026)
Background: Athlete motivation and sustained engagement are essential for retention in collegiate sports programs; however, the institutional and environmental factors that influence these outcomes remain underexplored. Objectives: This study aimed to examine the determinants of athlete motivation and engagement in collegiate team sports using a Self-Determination Theory perspective, with engagement serving as a proxy for retention behavior. Methods: A mixed-methods design was employed involving 75 collegiate student-athletes representing basketball, volleyball (men and women), baseball, and softball teams. Quantitative data were collected using a validated, researcher-developed questionnaire based on Self-Determination Theory and analyzed using descriptive statistics, Pearson’s correlation, multiple regression, and Structural Equation Modeling (SEM). In contrast, qualitative data were analyzed using thematic analysis. Results: Findings revealed that organizational commitment (M = 3.42) and environmental support (M = 3.47) were rated very high, while incentives and facilities were rated high. All program components were significantly associated with athlete engagement (p < .05). Regression analysis showed that environmental support (β = .36) and perceived support (β = .31) were the strongest predictors, explaining 68% of the variance (R² = 0.68). SEM results indicated a good model fit (CFI = 0.95; RMSEA = 0.061). Conclusions: Qualitative findings highlighted intrinsic motivations, such as passion and belonging, as well as extrinsic motivators, including scholarships and rewards, alongside barriers, including financial delays, academic conflicts, and burnout. The study concludes that environmental and perceived support are the primary determinants of athlete engagement, emphasizing the critical role of competence-supportive environments in sustaining motivation and improving athlete retention.